The Role of School Libraries in Enhancing Extensive English Language Reading Skills - Vuzo, Mwajuma (University of Dar es Salaam Library Journal, 2023)
Extensive reading enhances language ability. School libraries should expose English language learners to a range of interesting materials to promote language learning. The paper presents findings from a study on role of school libraries in enhancing extensive reading skills. It draws from the Tanzania context that represents English foreign language learning contexts. The objectives of the study included exploring the availability of school libraries and assessing how teachers and students use the school libraries to promote extensive English language reading skills. The respondents of this study were twelve English language teachers, one librarian and seventy-two students. Data were collected using interview, focus group discussions and observations. Krashen ' s comprehensible input theory informed the study. Findings showed that school libraries are available in some schools. School libraries available are not used by teachers and students to enhance learning of extensive reading skills in English language. Most of the school libraries do not have authentic materials to encourage interest in reading but old books, past papers and subject specific books. School libraries should be improved and built where necessary. They should be functional and well-equipped. This will encourage students to read extensively to improve their learning of English language through exposure to various language input. English subject teachers will consequently integrate the use of the school library to teach extensive reading skills.